Meningkatkan Pemahaman Literasi Finansial Pada Siswa SMK Pelita Gedong Tataan - Pipit Novila Sari; Astrid Aprica Isabella; Novalita Novalita; Regina Salsabila; Aura Dewi; Jahran Qaid Pratama (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
This community service activity was carried out by a Team of Lecturers and Students at the Faculty of Business at Mitra Indonesia University (UMITRA) Lampung for Students of Pelita Gedong Tataan Vocational School. This activity discusses increasing the understanding of financial literacy in Pelita Gedong Tataan Vocational School Students. This is done because financial literacy is very important to understand and apply in life, being one of the six basics of literacy. The goal is that every Pelita Gedong Tataan Vocational School student has an understanding of financial literacy that can be used not only at this time, but after they work and even have a household. The method used is socialization by providing motivation with lectures and discussions in the form of question and answer sessions. The results show that financial literacy is still a new knowledge for some students. Even though financial literacy greatly influences positive financial behavior and financial management itself. By participating in this activity, they hope to be able to increase financial literacy, and have an impact on good financial management and avoid various financial crimes.